Improved radiation risk models applied to different patient groups in Sweden - M. Andersson; K. Eckerman; D. Pawel; A. Almen; S. Mattsson (Радиационная гигиена)
In radiological diagnostics and therapy, it is important that practitioners, referrers, (i.e. radiologists, radiation oncologists and others in health-care) are aware of how much radiation a patient may receive from the various procedures used and associated health risk. The profession has a duty to inform patients or their representatives of the advantages and disadvantages of specific investigations or treatment plans. The need to estimate and communicate risks in connection with medical use of ionizing radiation is highlighted e.g. in the Russian Federation State Law No 3, §17.2,1996 and in the EU directive (2013/59/EURATOM 2014). The most commonly used way to express harm in relation to low doses of ionizing radiation is use of the quantity effective dose (E). Effective dose, a radiation protection quantity, however is not intended to provide risk estimates for medical exposures. Its purpose is to optimize conditions for radiation workers (18-65 years) or the general public; all groups with age distributions that differ from patients. In this paper the lifetime attributable risk was used to estimate the excess risk of receiving and dying of radiogenic cancer. The lifetime attributable risk estimations are generated from three different variables, gender, attained age and age at exposure giving the possibility to create age and gender specific cancer risk estimations. Initially, the US Environmental Protection Agency lifetime attributable risk coefficients which are intended to predict the cancer risk from ionizing radiation to a normal US population were applied. In this work, the lifetime attributable risk predictions were modified to the normal Swedish population and to cohorts of Swedish patients undergoing radiological and nuclear medicine examinations or treatments with survival times that differfrom the normal population. For Swedish males, all organs were given the same absorbed dose, exposed at 20, 40 and 70 years, the lifetime attributable risk coefficients (Gy-1) were 0.11, 0.068, and 0.038, respectively, which is lower than the corresponding figures for US males, 0.13, 0.077, and 0.040. For Swedish females, all organs were given the same absorbed dose, exposed at 40 years of age with a diagnosis of breast, colon or liver cancer, the lifetime attributable risk coefficients are 0.064, 0.034, and 0.0038, respectively, which is much lower than if a 40 years female without known cancer is exposed, 0.073.